A first 3-D shear wave velocity model of the Ischia Island (Italy) by HVSR inversion. Issue 3 (23rd April 2022) - Manzo, Roberto; Nardone, Lucia; Gaudiosi, Guido; Martino, Claudio; Galluzzo, Danilo; Bianco, Francesca; Di Maio, Rosa
SUMMARY: Following the M w 3.9 earthquake that occurred in the Ischia island (Naples, southern Italy) on 21 August 2017, the local monitoring seismic network was significantly improved in terms of both number of stations and instrumentation performance. Due to the huge amount of collected seismic ambient noise data, in this paper we present a first 3-D shear wave velocity model of the island retrieved from the inversion of horizontal-to-vertical spectral ratio curves by fixing the shear wave velocities ( Vs ) and modifying the thicknesses to get the corresponding 1-D Vs models. We are confident about the robustness of the attained models since the inversion process provided a good convergence towards the best-fitting solutions. Then, a first 3-D velocity model was obtained by contouring all the 1-D models obtained for the selected seismic stations to highlight possible lateral variations of the layer thicknesses and to reconstruct the morphology of the deeper interface characterized by a high-impedance contrast. A good correspondence between the 3-D Vs model and the geological features of the island was observed, especially in the northern sector where most of the stations are installed. In particular, the top of the high-impedance contrast interface appears deeper in the northern coastal areas and shallower in the central sector. This result agrees with the structural settings of the island likely due to the resurgence of Mount Epomeo.